Evaluasi Efektivitas Kurikulum Merdeka dalam Pendidikan Olahraga di Era Digital - Ajito, Timoteus; Ratnaya, I Gede; Mola, Mansuetus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to evaluate the effectiveness of the Merdeka Curriculum in sports education, especially in the context of the digitalization of learning. Using a qualitative descriptive method, the study involved three Physical Education, Sports, and Health (PJOK) teachers at SMK Negeri 3 Kupang City as resource persons. Research data was collected through questionnaires and interviews, which will then be analyzed by the researcher through a triangulation process, which includes source and technique triangulation. The study results indicate that PJOK teachers are well prepared to utilize digital media as a learning tool. However, there is a need to improve knowledge and skills in using more complex digital media and the experience of integrating these media into the learning process. These findings are expected to be an important reference for education stakeholders in formulating strategies and policies to improve the quality of sports learning in the digital era. Thus, this study significantly contributes to the development of adaptive and effective sports education.